1993
DOI: 10.1530/acta.0.1280361
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor stimulates the prolactin synthesis and secretion in rat pituitary cells in culture (GH4C1 cells) by increasing the intracellular concentration of free calcium

Abstract: Epidermal growth factor (EGF) stimulated the prolactin (PRL) synthesis and release from the GH4C1 cells in a dose-dependent manner. The ED50 was between 10−11 and 10−10 mol/l. The maximal effect was obtained at 10−9 mol/l EGF for the release, and 10−8 mol/l EGF for the synthesis. EGF stimulated the release of PRL from cell perfusion columns after a lag period of about 30 s. The maximal secretion of PRL occurred about 60 s after the start of stimulation. The PRL secretion declined to basal levels within 2 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…24 In the light of the putative mechanism underlying EGF actions in triggering this pathway, the question of a possible calpain (or other Ca 2+ -dependent proteases) involvement appears particularly important since it has been reported that an increase in the intracellular Ca 2+ concentrations mediates EGF effects on GH4C1 cells. 25 More generally, the results presented here taken together with the previously published data suggest a dual involvement of L-DNaseII in both apoptosis 15,17,19 and paraptosis (present study). It should be stressed that a dual involvement of CAD in both apoptosis and necrosis has also been reported in ischemic hippocampal neurons.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…24 In the light of the putative mechanism underlying EGF actions in triggering this pathway, the question of a possible calpain (or other Ca 2+ -dependent proteases) involvement appears particularly important since it has been reported that an increase in the intracellular Ca 2+ concentrations mediates EGF effects on GH4C1 cells. 25 More generally, the results presented here taken together with the previously published data suggest a dual involvement of L-DNaseII in both apoptosis 15,17,19 and paraptosis (present study). It should be stressed that a dual involvement of CAD in both apoptosis and necrosis has also been reported in ischemic hippocampal neurons.…”
Section: Discussionsupporting
confidence: 87%
“…The latter hypothesis implies a hyperactivation of EGFR expressed on GH4C1 cells by a physiological concentration of EGF since we used this trophic factor in a nanomolar concentration (corresponding to the affinity of pituitary EGFR). 25,30 Future studies focused on the analysis of the functional consequences of such putative EGFR hyperactivation will certainly help understanding the molecular mechanisms linked with EGFassociated malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The EGF-R has an intrinsic tyrosine kinase activity, and inhibition of tyrosine kinase activities has recently been shown to decrease [ 3 H]thymidine uptake in primary cultures of human pituitary adenomas ( Jones et al 1997). EGF can modulate the secretion of pituitary hormones in both normal (Ikeda et al 1984, Miyake et al 1985, Childs et al 1991 and tumor pituitary cells (Schonbrunn et al 1980, Aanestad et al 1993. Transforming growth factor-(TGF-), a member of the EGF family, which can thus also act through the EGF-R on target cells, has been detected in the normal pituitary gland (Kobrin et al 1987, Ezzat et al 1995, Fan & Childs 1995, and has been implicated in pituitary tumorigenesis (Finley & Ramsdell 1994).…”
Section: Introductionmentioning
confidence: 99%
“…P. Mellon (University of California, San Diego, San Diego, CA) and D. Weiner (University of California, San Francisco, San Francisco, CA). This cell line was grown in DMEM supplemented with 10% fetal bovine serum.For hormone assays, cells were cultured in the presence of 1 nM EGF (Sigma-Aldrich, St. Louis, MO) concentration based on the previous reports by using pituitary (Birman et al, 1987) cells, including GH4C1 cell line (Aanestad et al, 1993). Nerve growth factor (NGF) (Sigma-Aldrich) was chosen as a negative control for EGF actions because these two growth factors use partly overlapping transduction pathways but induce morphologically and biochemically distinct cellular responses both in nonrelated (Huff and Guroff, 1981) and somato-lactotrope (Yoshinaga et al, 1998) cell lines.…”
mentioning
confidence: 99%